2019
DOI: 10.1016/j.landurbplan.2019.103638
|View full text |Cite
|
Sign up to set email alerts
|

Natural neighbourhood environments and the emotional health of urban New Zealand adolescents

Abstract: Natural neighbourhood environments and the emotional health of urban New Zealand adolescents. Landscape and Urban Planning, 191, article no. 103638.For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 47 publications
3
32
1
Order By: Relevance
“…Studies demonstrated that higher NDVI with a 1250, 500 and 300 m buffer surrounding the home address had associations with lower depression, stress and SPD [ 20 , 49 , 56 ]. This finding aligns with a New Zealand study published after the search, which found significant relationships between reduced depressive symptoms in adolescents and increased mean greenness (NDVI) in residential neighbourhoods (defined as 400 and 800 m buffers around meshblock boundaries) [ 60 ]. Authors also reported a negative association between variability in greenness in 1600 m buffer and adolescents’ well-being.…”
Section: Discussionsupporting
confidence: 89%
“…Studies demonstrated that higher NDVI with a 1250, 500 and 300 m buffer surrounding the home address had associations with lower depression, stress and SPD [ 20 , 49 , 56 ]. This finding aligns with a New Zealand study published after the search, which found significant relationships between reduced depressive symptoms in adolescents and increased mean greenness (NDVI) in residential neighbourhoods (defined as 400 and 800 m buffers around meshblock boundaries) [ 60 ]. Authors also reported a negative association between variability in greenness in 1600 m buffer and adolescents’ well-being.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we found the direct positive effects of perceived street walkability on positive moods. Consistent with this, previous research has shown that viewing a good-quality street environment containing pleasant elements (i.e., trees, light, clean pavement, and street furniture) could promote a positive mood and enhance a sense of pleasure [ 17 , 99 , 100 , 101 ]. On the other hand, the perception of complexity and poor material conditions in the outdoor environment may have side effects that diminish positive mood [ 102 , 103 ].…”
Section: Discussionsupporting
confidence: 70%
“…In previous studies, we also confirmed that natural materials such as vegetation have a significant correlation with the duration of children's activity in the spatial environment. They can promote the duration of and intensity children's physical activity, and children with longer outdoor activity times have higher cardiopulmonary fitness ( 44 ) and better children's physical and mental health development ( 45 , 46 ). However, there are few children's activity places with natural materials in the urban neighborhood space, which shows a significant deviation between children's own needs, the actual construction of the city and the habitual neglect and deprivation of children's rights ( 25 ).…”
Section: Discussionmentioning
confidence: 99%